Arah Politik Hukum Nasional Terhadap Kesejahteraan Sosial Dalam Kerangka Konstitusi Ekonomi Di Indonesia - Fuqoha Fuqoha (Universitas Serang Raya, 2021)
Economic constitution has become a new idea within the constitutional framework as the basic foundation for the development of the national and global economy. National economic policies in the context of realizing social welfare must be able to guard and control the national economic system. Apart from the legal politics policy and the government's power in determining the direction of national policy, the conception of the economic constitution as the basic foundation must be realized. This study intends to describe the politics of national law and the concept of economic constitution in realizing social welfare. This research method uses normative juridical research using an exploratory descriptive analytical approach. The characteristics of national legal politics in practice still influence the realization of national economic policies, even though it has implied the concept of an economic constitution in the 1945 constitution. Social welfare, which is the goal of the state, becomes a political tool for national law through a national economic system that cannot be separated from political power.